Comparação entre fosfatos aplicados ao feijoeiro: I- Trabalhos em casa de vegetação - Mário Braga, José (Revista Ceres, 2025)
Several sources of phosphorus applied inbeans (Phaseolus vulgaris L. cv, 'Rico23') were studied in greenhouse, in comparative study in Viçosa, Minas Gerais, Theyare simple superphosphate, di-ammonium phosphate, bones flour, termophosphate, Araxa phosphate and phosphoric acidat thelevels of 100, 200 and 300 kg. of P,Og per hectare. The sources of phosphorus were compared by the value of the slope of the regression line. Using the value of simple superphosphate as an index, the results showedthat dirammonium phosphate had the highest value for disponibility coefficient following termophosphate, phosphoric add ,and Araxá phosphate, Bone flour hada negative value.